Tumour but not stromal expression of β3 integrin is essential, and is required early, for spontaneous dissemination of bone‐metastatic breast cancer. Issue 5 (7th January 2015) - Carter, Rachel Zoe; Micocci, Kelli Cristina; Natoli, Anthony; Redvers, Richard Paul; Paquet‐Fifield, Sophie; Martin, Ana Carolina Baptista Moreno; Denoyer, Delphine; Ling, Xiawei; Kim, Soo‐Hyun; Tomasin, Rebeka; Selistre‐de‐Araújo, Heloisa; Anderson, Robin Lesley; et al.
Abstract: Although many preclinical studies have implicated β 3 integrin receptors ( α v β 3 and α IIb β 3) in cancer progression, β 3 inhibitors have shown only modest efficacy in patients with advanced solid tumours. The limited efficacy of β 3 inhibitors in patients could arise from our incomplete understanding of the precise function of β 3 integrin and, consequently, inappropriate clinical application. Data from animal studies are conflicting and indicate heterogeneity with respect to the relative contributions of β 3‐expressing tumour and stromal cell populations in different cancers. Here we aimed to clarify the function and relative contributions to metastasis of tumour versus stromal β 3 integrin in clinically relevant models of spontaneous breast cancer metastasis, with particular emphasis on bone metastasis. We show that stable down‐regulation of tumour β 3 integrin dramatically impairs spontaneous (but not experimental) metastasis to bone and lung without affecting primary tumour growth in the mammary gland. Unexpectedly, and in contrast to subcutaneous tumours, orthotopic tumour vascularity, growth and spontaneous metastasis were not altered in mice null for β 3 integrin. Tumour β 3 integrin promoted migration, protease expression and trans‐endothelial migration in vitro and increased vascular dissemination in vivo, but was not necessary for bone colonization in experimental metastasis assays. We conclude that tumour, rather than stromal, β 3 expression is essential and is required early for efficient spontaneous breast cancer metastasis to bone and soft tissues. Accordingly, differential gene expression analysis in cohorts of breast cancer patients showed a strong association between high β 3 expression, early metastasis and shorter disease‐free survival in patients with oestrogen receptor‐negative tumours. We propose that β 3 inhibitors may be more efficacious if used in a neoadjuvant setting, rather than after metastases are established. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.